COMING FULL CIRCLE IN 20 YEARS: A Synthesis of the DWDS Field Instruction Program Experience - Barraneda, Teresita V. (Philippine Journal of Social Development; 2007, 2010)
This article discusses the birthing of the Department of Women and Development Studies in parallel with the herstory of the Field Instruction Program or fieldwork to many students. This article is a synthesis of the DWDS 20th experience in doing fieldwork practice that were drawn out from the fieldwork assessments and sharing sessions, interviews with fieldwork students and partner agencies, and other DWDS documents and reports. As a synthesis paper it highlights the strengths and issues confronting the FIP, in particular, its impact to students, FIP administration and management, fieldwork placements, the partner agencies and students’ contributions to these agencies. The article ends up by posing some questions and challenges to the DWDS as it embarks on a new phase of its journey in promoting women’s studies.